Evaluation of Lipid Profile in Patients with Cardiovascular Diseases Receiving Simvastatin in Palu Indonesia - Safarudin; Alwiyah Mukaddas; Faraditha Amalia; Amelia Rumi (Journal of Pharmacy and Nutrition Sciences, 2018)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide which results from the impaired function of the heart and blood vessels. The most common CVDs are coronary heart and stroke. The main clinical manifestation of these diseases is the formation of atherosclerosis which is associated with the change of blood lipid levels. Simvastatin is widely used in patients with impaired lipid levels in the blood. The study was a descriptive research with a retrospective approach on medical record data (n=64) taken from Palu City, Central Sulawesi, Indonesia. The variables included in this study were gender, age, diagnosis, co-medication, lipid profile including total cholesterol, LDL, triglycerides, and HDL in patients with CVDs receiving simvastatin. In the study, sixty-four patients of CVDs met the inclusion and exclusion criteria. This study suggested that simvastatin achieved to normalize the blood lipid levels, including total cholesterol in forty-four patients (68.75%), LDL in forty-nine patients (80.3%), triglycerides in fifty-nine patients (92.19%), and HDL in fifty-two patients (81.25%). The use of simvastatin in patients with CVDs managed to lower total cholesterol, LDL, and triglycerides, as well as increase the HDL level.